2012
DOI: 10.1093/molehr/gas005
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of bitter taste transduction leads to massive spermatid loss in transgenic mice

Abstract: Bitter taste perception is an important sensory input warning against the ingestion of toxic and noxious substances. Bitter receptors, a family of ~30 highly divergent G-protein-coupled receptors, are exclusively expressed in taste receptor cells that contain the G-protein α-subunit gustducin, bind to α-gustducin in vitro, and respond to bitter tastes in functional expression assays. We generated a taste receptor type 2 member 5 (T2R5)-Cre/green fluorescent protein reporter transgenic mouse to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 27 publications
0
62
0
Order By: Relevance
“…It is noteworthy that TRPM5 is expressed in taste receptor cells and other chemosensory cells of the taste signaling cascade in the vomeronasal organ, olfactory epithelium, brainstem, enterocrine cells in stomach, duodenum, large intestine, respiratory tract, and pancreatic b cells (see Nilius and Appendino, 2013). Furthermore, TRPM5 expression was reported in the testis, where it is believed to be involved in spermatogenesis (Li and Zhou, 2012).…”
Section: +mentioning
confidence: 99%
“…It is noteworthy that TRPM5 is expressed in taste receptor cells and other chemosensory cells of the taste signaling cascade in the vomeronasal organ, olfactory epithelium, brainstem, enterocrine cells in stomach, duodenum, large intestine, respiratory tract, and pancreatic b cells (see Nilius and Appendino, 2013). Furthermore, TRPM5 expression was reported in the testis, where it is believed to be involved in spermatogenesis (Li and Zhou, 2012).…”
Section: +mentioning
confidence: 99%
“…In light of findings showing that Tas2r are present in organs that are not at all or only partially accessible to xenobiotics, such as brain (86 -89), testes (61,90,91), thyroid (92), and urethra (93), we also examined whether hormones could function as Tas2r activators. We found that progesterone stimulated Tas2r114 and Tas2r110.…”
Section: Substancementioning
confidence: 99%
“…Mouse spermatids and spermatozoa respond to bitter compounds with calcium signaling in an ␣-gustducin-dependent manner (61). Genetic ablation of bitter receptor cells in mice causes massive spermatid loss (90). Further studies are needed to elucidate the role of this and other Tas2r in testicular function.…”
Section: Substancementioning
confidence: 99%
“…As all 35 mouse bitter taste receptor genes are expressed in the testis and it was shown that mouse spermatids respond to several bitter compounds with increases of intracellular calcium levels [43], it would be highly interesting to see if also bitter taste receptor agonists and antagonists may affect male fertility. The generation of a mouse line, in which all cells that express the bitter taste receptor gene Tas2r105 are genetically ablated by the expression of diphtheria toxin A, revealed a considerable reduction in testicular size [40]. However, this mouse line still produces a reduced number of spermatids including Tas1r3-positive spermatids, suggesting a heterogeneous population of sperm cells.…”
Section: Heartmentioning
confidence: 99%
“…It was shown that α-gustducin expression occurs already in differentiating spermatids and is retained in mature spermatozoa [167]. Moreover, also other components of the gustatory signaling cascade, involved in signal transduction of taste GPCRs such as Gγ13, phospholipase Cβ2, and the transient receptor potential channel TRPM5, have been identified in mouse sperm cells [40]. Indeed, expression of all 3 Tas1r genes and all 35 putatively functional Tas2r genes has been detected in mouse testes [43].…”
Section: Heartmentioning
confidence: 99%